Problematika Putusan Mahkamah Konstitusi Nomor 106/Puu-Xviii/2020 Dalam Judicial Riview Undang-Undang Narkotika Terkait Ganja Medis - Rianida, Puja; Sianturi, Catherine Rosalina; Amalia, Firda; Putri, Dwi Cinta Wiliananda (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Judicial Review Application of the Narcotics Law regarding medical marijuana has raised a major issue in the Constitutional Court Decision Number 106/PUU-XVIII/2020. The decision rejecting the legalization of medical marijuana has caused confusion between the constitutional right to health and efforts to combat drug abuse. This study explores the various problems that arise from the decision, including the lack of sufficient scientific support for the therapeutic benefits of marijuana, obstacles to innovation in the medical field, and regulatory deficiencies that hinder research development and patient access. The rejection by the Constitutional Court also raises discussions about the role of the judiciary in responding to scientific developments, as well as comparisons with policies in other countries that have legalized the use of medical marijuana. This analysis emphasizes the importance of finding a balance between prohibition policies and approaches that respect human rights, as well as the long-term effects of the decision on health and legal policies in Indonesia. This study will discuss How are the judges' considerations in decision number 106/PUUX-VIII/2020 regarding the medical marijuana application? and What is the mechanism for the application in the judicial review of the medical marijuana law